Aliran kerapatan di sungai akibat intrusi air asin. - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Kawasan dan Pedesaan Universitas Gadjah Mada, 1999)
ABSTRACT Fresh water have less density than salt water. If these two fluids with different densities are _flowing in a channel, then a mixed flow may occur. The Interaction between fresh and salt water depends on the Mixing Ratio .411 as a product of the fresh water flow and the tide period over the tidal prism (1..lassie,1976). Three types of mixed water flows in a river were previously considered, i.e., fully mixed flow, partially mixed flow and stratified flow. The type of mixed flow can be, e.g., characterized by dimensionless Estuary Number E (Harleman dan Abraham,1966) which depends on the Froude Number, or by Mixing Coefficient (Furumoto and Awaya,1988) also depending on the Stratified Froude Number, as well as by Gradient Richardson Number K (French,1986) where the flow in an open channel is classified in a range between homogenous and stratified by density gradient. The numerical simulation was developed from volume continuity, salinity continuity and momentum equations. Those equations are consider with kinematic viscosity and diffusion. The .field measurements have been taken in several cross sections of Lamong River in Indonesia (Anwar, et al, 1992) as well as Nanakita River in Japan (Uehara,1984). Analysis were done by identifying those rivers by the mixing conditions and numerical simulations. According to the mixing conditions, Lamong River was concluded to be fully mixed flow since having small mixing ratio and, on the contrary, Nanakita River was concluded to be stratified flow with highly mixing ratio. The result of numerical simulation is that the Officer's Equation (of kinematic viscosity and diffusion) is recommended to be used for fully mixed flow conditions such as Lamong River, on the other hand, the Van Rees's Equation is recommemded to be used for fully stratified flow types such as Nanakita River.